The Empowerment of Mosque-Based Micro, Small, and Medium Enterprises (MSMEs) with a Marketpreneur Approach and Maqashid Syariah - Fathma, ‘Azizah; Rizki, Darlin; Fatimah, Rika (International Journal of Nusantara Islam, 2024)
Mosques have experienced a decline in function and role. However, in the midst of the degradation of the role of mosques, the Jogokariyan Mosque continues to make efforts to revive mosques through micro, small, and medium enterprise (MSME) empowerment programs. The aim of this research is to analyze mosque-based empowerment activities using a marketpreneur approach and measure the achievements of maqashid sharia among MSMEs assisted by mosques. The research utilized a descriptive quantitative approach with questionnaires and interviews as survey methods. The sampling used a non-probability sampling approach with a convenience sampling technique. The total samples consisted of 66 MSMEs assisted by the Jogokariyan Mosque. The research results revealed that the Jogokariyan Mosque has fulfilled the marketpreneur’s key measurements, namely business chain strategies and market projections. The business chain strategy activities carried out included coaching via WhatsApp groups, business lessons, and capital assistance. Meanwhile, the market projections implemented were forming partnerships, participating in bazaars, and joining community markets. Through the maqashid sharia approach, two aspects were obtained, namely the spirituality aspect and the business growth aspect. The spirituality aspect shows that business actors have fulfilled the indicators of maintaining religion, self, family, and intellectual with high values. Meanwhile, in terms of business growth, it is still at a moderate level. However, the MSME actors under the support of the Jogokariyan Mosque have overall achieved maqashid sharia.